Molecular cloning of rat renin cDNA and its gene. - Burnham, C E (1987)
Renin (EC 3.4.23.15) is an aspartyl protease that cleaves its only known substrate, angiotensinogen, to release the vasopressor hormone angiotensin. We have isolated full-length cDNAs for renin from a rat kidney cDNA library. The cDNAs are complementary to a 1434-nucleotide rat kidney mRNA that encodes preprorenin, the 402-amino acid precursor of renin. This rat cDNA was used to isolate the complete copy of a renin gene from a rat genomic library, and a comparison of this genomic clone with rat genomic DNA showed that renin is a single-copy gene in the rat. Rat renin is 85% identical to one mouse renin isozyme (renin-1) and 81% identical to the second mouse renin isozyme (renin-2), suggesting that the duplication of the mouse renin genes is a more recent event than the speciation of rats and mice. Analyses of rat, human, and mouse renin sequences revealed that the potential to form two-chain renin is apparently peculiar to mouse renin, and the expression of a tenth exon (which results in a three-amino acid insertion) is observed only in the human renin gene.